Psychological Distress and Coping Strategies Among Primary School Teachers in Nsukka Local Government Area, Enugu State - Ogundu, Levi; Agbaje, O.S.; Nwoko, Ifeoma Emmanuela (International Journal of Human Kinetics, Health and Education, 2023)
This study investigated psychological distress and coping strategies among primary school teachers in Nsukka LGA, Enugu State. The study adopted a descriptive cross-sectional survey research design. The population for the study comprised all 914 primary school teachers in Nsukka LGA. The sample size for the study was 280 primary school teachers. The study adopted multi-stage sampling procedure to draw the sample for the study. The instruments for data collection were General Health Questionnaire 12 item version (GHQ-12), and Brief Coping Orientation for Problem Experiences (Brief COPE). Data analyses were conducted using the SPSS version 20. Descriptive statistics, simple and multiple linear regressions were tools employed for data analyses. The findings showed that primary school teachers had a high level of psychological distress (M = 25.9; SD = 13.93), the primary school teachers in Nsukka adopted problem-focused coping strategies (M = 2.37; SD = 1.26). Age, Gender, and Educational and qualification were significantly related to teachers’ psychological distress (p < 0.05), as increase in teachers age was associated with decrease in teachers experience of psychological distress, and increase in the teachers’ educational qualification is associated with decrease in psychological distress among the teachers. The authors recommended among others that government should provide a conducive working environment, furniture, toilet facility, good offices and classrooms for pupils and primary school teachers.